Carboxymethyl cellulose film from durian rind - Rachtanapun P. (2014)
Cellulose from durian rind was converted to carboxymethyl cellulose (CMC d) by carboxymethylation using sodium monochloroacetate (SMCA) and various sodium hydroxide (NaOH) concentrations (20-60 g/100 mL). The chemical structure of the cellulose and resulting polymers was then characterized using Fourier transform infrared spectroscopy (FTIR). Then, the properties of the CMC d materials were investigated. The optimum condition for carboxymethylation was found to be 30 g/100 mL NaOH, which provided the highest viscosity and degree of substitution (DS = 0.87). Crystallinity of CMC d was found to decline after synthesis. The L* value of the CMC d decreased with increasing NaOH concentrations (20-40 g/100 mL). The trend of the a* and b* values varied inverses to the L* values. The CMC d films were prepared and tested, and the highest tensile strength (140.77 MPa) and WVTR (220.85 g/day·m 2) were found using the 30 g/100 mL NaOH-synthesized CMC d film. The percent elongation at break of the different CMC d films was not to significantly differ. © 2012 Elsevier Ltd.